Phytochemical screening and antibacterial effect of phenolic extracts from two Mediterranean Cupressus - Degaïchia, Hoceme; Moualhi, Noussaiba; Benhamadi, Meriem; Benrima, Atika (Revista Mexicana de Ciencias Agrícolas, 2022)
The objective of our research is to identify the chemical components and evaluate in vitro, the antibacterial activity of the extracts from the leaves of Cupressus sempervirens L. and Cupressus arizonica L. from northern Algeria against Pseudomonas aeruginosa ATCC 9027. The extraction was carried out by macerating the leaves in solvents of increasing polarity (chloroform, petroleum ether and aqueous methanol). A screening of the phenolic compounds was carried out for a qualitative characterization of the different extracts. The extracts obtained were put in contact with a strain of P. aeruginosa to determine their antibacterial potential. Phytochemical screening revealed the presence of several secondary metabolites: leucoanthocyanins, flavonols, flavonones, anthraquinones, catechin tannins, gallic tannins, steroids, triterpenes, saponin, cardiac glycosides, terpenoids, saponosides and free quinones. Aqueous methanol (high polarity) allows the extraction of most metabolites. The best extraction yield of the three solvents is chloroform, with an extraction yield of 61.23% (for C. sempervirens) and 52.27% (for C. arizonica), followed by the hydroalcoholic solvent 33.55% and the ethereal solvent with 0.39%. Hydroalcoholic extraction induces a very important sensitivity of P. aeruginosa, with a diameter of 16.2 mm for C. arizonica. Ethereal and chloroformic extracts induce weak inhibition. P. aeruginosa is extremely sensitive to the hydroalcoholic extract from C. sempervirens, the latter induces an inhibition zone with a diameter of 19.95 mm, which is statistically equal to that induced by Vancomycin. These results can be considered as a promising solution for the replacement of vancomycin with the hydroalcoholic extract from C. sempervirens.
Keywords: Cupressus arizonica; Cupressus sempervirens; Pseudomonas aeruginosa; hydroalcoholic extract